2004
DOI: 10.3758/cabn.4.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Cortical regions associated with different aspects of object recognition performance

Abstract: In the present object recognition study, we examined the relationship between brain activation and four behavioral measures: error rate, reaction time, observer sensitivity, and response bias. Subjects perceptually matched object pairs in which structural similarity (SS), an index of structural differentiation, and exposure duration (DUR), an index of task difficulty, were manipulated. The SS manipulation affected the fMRI signal in the left anterior fusiform and parietal cortices, which in turn reflected a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
(103 reference statements)
3
9
0
Order By: Relevance
“…Wheeler et al [2] reported reactivation of visual information in the left fusiform gyrus, and suggested that its activation is related to processing forms, colors, and texture of objects. In slight contrast, the left as well as the right fusiform gyri are activated during recognition of visual information such as pictures [17]. Cabeza and Nyberg [18] suggested that neural activation of border areas between the temporal and the occipital lobes, including the fusiform gyrus, plays a role in processing visual sensory input as well as visual imaging.…”
Section: Discussionmentioning
confidence: 98%
“…Wheeler et al [2] reported reactivation of visual information in the left fusiform gyrus, and suggested that its activation is related to processing forms, colors, and texture of objects. In slight contrast, the left as well as the right fusiform gyri are activated during recognition of visual information such as pictures [17]. Cabeza and Nyberg [18] suggested that neural activation of border areas between the temporal and the occipital lobes, including the fusiform gyrus, plays a role in processing visual sensory input as well as visual imaging.…”
Section: Discussionmentioning
confidence: 98%
“…To allow subjects to view the object and their hand touching the object simultaneously, we manipulated effectiveness by changing the level of similarity among the objects and thus the difficulty of object recognition. There is evidence to suggest that increasing the level of similarity produces changes in effectiveness in object-selective brain regions in the desired direction for assessing inverse effectiveness ( Joseph & Farley, 2004). Thus, in the present experiment, we varied the level of behavioral performance and BOLD activation effectiveness by changing the similarity between objects, rather than by degrading them.…”
Section: Introductionmentioning
confidence: 96%
“…Matching of objects may also involve semantic processing, but it is not required for the matching task (in Figure 1, semantic processing is parenthesized). The degree of structural and perceptual similarity between nonmatching stimuli was parametrically varied as in Joseph and Farley (2004) and Joseph and Gathers (2003) to tap into the process of fine differentiation. Higher levels of similarity were expected to induce higher functional magnetic resonance imaging (fMRI) signal in brain regions involved in fine differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The second question is whether making fine distinctions among visually similar objects is specifically associated with mid-fusiform activation (Rogers et al, 2005; Gerlach, Law, & Paulson, 2004; Joseph & Farley, 2004; Joseph & Gathers, 2003; Price, Noppeney, Phillips, & Devlin, 2003; Gauthier et al, 1999; Gerlach, Law, Gade, & Paulson, 1999; Damasio, Grabowski, Tranel, Hichwa, & Damasio, 1996). Objects within the same category tend to overlap at the level of structural descriptions; consequently, the process of fine differentiation of objects (e.g., distinguishing different breeds of dogs) will require making fine distinctions among structural descriptions.…”
Section: Introductionmentioning
confidence: 99%